Planarized B, N-phenylated dibenzoazaborine with a carbazole substructure: electronic impact of the structural constraint. Issue 22 (21st May 2019) - Ando, Mikinori; Sakai, Mika; Ando, Naoki; Hirai, Masato; Yamaguchi, Shigehiro
Abstract : Structural constraint in B, N -phenylated dibenzoazaborine alters the π-conjugation mode and furnishes intense deep-blue emission and intriguing electrochemical properties. Abstract : A B, N -diphenyl-5, 10-dihydro-dibenzo-1, 4-azaborine, in which both phenyl groups on the boron and nitrogen atoms are planarized to generate a carbazole substructure, was synthesized. The structral constraint around the boron and nitrogen atoms alters the π-conjugation mode and thus the photophysical and electrochemical properties. Specifically, this structurally constrained dibenzoazaborine showed an intense blue emission with a narrow full width at half maximum. One of its derivatives exhibited near infrared absorption in the one-electron-oxidized state.